Hyperforin Potentiates Antidepressant-Like Activity of Lanicemine in Mice - Pochwat, Bartłomiej; Szewczyk, Bernadeta; Kotarska, Katarzyna; Rafało-Ulińska, Anna; Siwiec, Marcin; Sowa, Joanna E.; Tokarski, Krzysztof; Siwek, Agata; Bouron, Alexandre; Friedland, Kristina; Nowak, Gabriel (Frontiers in Molecular Neuroscience, 2018)
N-methyl-D-aspartate receptor (NMDAR) modulators induce rapid and sustained antidepressant like-activity in rodents through a molecular mechanism of action that involves the activation of Ca2+ dependent signaling pathways. Moreover, ketamine, a global NMDAR antagonist is a potent, novel and atypical drug that has been successfully used to treat major depressive disorder (MDD). However, because ketamine evokes unwanted side effects, alternative strategies have been developed for the treatment of depression. The objective of the present study was to determine the antidepressant effects of either a single dose of hyperforin or lanicemine versus their combined effects in mice. Hyperforin modulates intracellular Ca2+ levels by activating Ca2+-conducting the non-selective canonical transient receptor potential 6 channel (TRPC6) channels. Lanicemine, on the other hand, blocks NMDARs and regulates Ca2+ dependent processes. To evaluate the antidepressant-like activity of hyperforin and lanicemine, a set of in vivo (behavioral) and in vitro methods (western blotting, Ca2+ imaging studies, electrophysiological and radioligand binding assays) was employed. Combined administration of hyperforin and lanicemine evoked long-lasting antidepressant-like effects in both naïve and chronic corticosterone-treated mice while also enhancing the expression of the synapsin I, GluA1 subunit and brain derived neurotrophic factor (BDNF) proteins in the frontal cortex. In Ca2+ imaging studies, lanicemine enhanced Ca2+ influx induced by hyperforin. Moreover, compounds such as MK-2206 (Akt kinase inhibitor) inhibited the antidepressant-like activity of hyperforin in the tail suspension test (TST). Hyperforin reversed disturbances induced by MK-801 in the novel object recognition (NOR) test and had no effects on NMDA currents and binding to NMDAR. Our results suggest that co-administration of hyperforin and lanicemine induces long-lasting antidepressant effects in mice and that both substances may have different molecular targets.